Fenomena joget viral di tiktok: mengapa generasi muda indonesia gemar menari online? - Darmayanti, Silvi Nur Afifa (Maliki Interdisciplinary Journal, 2025)
The viral dance phenomenon on TikTok has become a very popular trend among the younger generation. This article discusses the factors that drive the enthusiasm of the younger generation in following the dance trend on TikTok, as well as the positive impacts it has. The main factors that influence the interest of the younger generation in dancing on TikTok include the influence of popular culture and globalization, the desire to go viral and gain social recognition, and the role of sophisticated algorithms that support the widespread spread of trends. TikTok has created a digital environment that allows its users to participate in various dance challenges and showcase their creativity to a wider audience. In addition, this phenomenon also has a positive impact on its users. TikTok not only functions as a medium for entertainment, but also as a place to express creativity that allows users to create new choreography and explore various types of dance. Participation in the dance trend on TikTok has also been shown to increase self-confidence and expand social interactions for the younger generation, especially with communities that share the same interests. Furthermore, dancing activities on TikTok have benefits for physical health, because they indirectly encourage physical activity that can improve physical fitness. The viral dance trend on TikTok is not just entertainment, but also has a broader impact on social, cultural, and health aspects. Therefore, it is important for users to utilize this platform wisely and productively, such as by using it as a means of education and promotion of local culture.